Profile of visual impairment in older adult patients attending primary eye care optometry clinic : a retrospective study - Mohd Harimi Abd Rahman,; Anis Humaira’ A,; Norliza MF,; Zainora Mohammed,; Nur Syafiqah S,; Qiu, TK (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
With an aging population, prevalence of visual impairment (VI) is expected to increase as well. A retrospective study was conducted involving the files of older adult patients aged 60 years and above from the Primary Eye Care (PEC) Optometry Clinic Universiti Kebangsaan Malaysia (UKM). This study was aimed to determine the prevalence and causes of VI among older adults. This retrospective study was conducted by reviewing files of older adult patients aged 60 years and above who had visited PEC Optometry Clinic UKM from 2009 to 2019. Socio-demographic, health status, status of visual acuity (VA), refractive error, prevalence and causes of VI before and after refractive correction were analysed by using descriptive statistic. Habitual distance VA was measured monocularly using the Snellen chart and recorded in decimal unit. The mean habitual distance VA in the better eye was 0.72+0.31, ranging from 0.41 to 1.03 while the mean VA after subjective refraction in the better eye was 0.88+0.28 which ranging from 0.60 to 1.16. The prevalence of VI based on habitual VA were 16.0%. The main cause of VI based on habitual VA was cataract (53.4%). The refractive status after subjective refraction showed highest percentage of hyperopia (41.9%), followed by emmetropia (32.4%) and myopia (25.7%). The findings of this study emphasise the importance of increased patient education and further expansion of optometric services are required to reduce avoidable blindness.